Merit as the main source of the provision of administrative career employment in Colombia (2019)
The main objective of the National Civil Service Commission - CNSC, is the administration of the administrative career system in Colombia. To fulfill their mission objectives, they are supported by duly accredited educational institutions. However, in the calls developed, it is observed that the level of distrust by civil society to these processes is high; due to the noise generated by issues such as: corruption, clientelism and the way in which the acts of organizational structuring are carried out through the drafting of the Manuals of Labor Functions and Competencies - MFCL of the territorial and national entities. In this sense, it is intended through this critical essay to determine whether the meritocracy principle has contributed to the provision of administrative career jobs in Colombia. Under this context, the research question is answered through a normative analysis of the technical system of administrative career and a comparison between two examples of public calls, showing that although it is true there have been variations in the form of administration of the staff; This is not the main problem of employment provision; as there are factors that go beyond the regulations such as the competence of the Administrative Department of the Public Function regarding the organic control of the entities that carry out their MFCL and the CNSC who is the one who must make the public calls assuming the difficulties that these administrative acts bring. Taking this into account, it is recommended that the DAFP assume a role rather than control and surveillance of territorial entities in the organic update that they perform for personnel administration, in the same way; that the civil organization assumes a more active role in the provision of jobs through social control through constitutional tools such as citizen oversight.